Analysis of Nutritional Status and Macronutrient Intake in Toddlers in Matraman District, East Jakarta - Rita Fitriyanti; Ratih Agustina Prikhatina; Slamet Santoso Kurniawan; Ratna Mutu Manikam; Titi Indriyati (Jurnal Ilmiah Kesehatan, 2026)
In supporting the improvement of community nutrition, it is necessary to collect data as an effort to analyze problems so that it is easier to find the priority of the problem. From some of the problems obtained, an analysis of the causes of the problem can be carried out. Problem-solving is carried out by preparation and planning with the aim of improving community problems, especially in Matraman District, East Jakarta City, in 2025. The purpose of this study is to find out the characteristics, nutritional status, intake of macro and micro nutrients, and nutritional knowledge in the target group, namely toddlers. This study uses a cross-sectional design with a population of all toddlers aged 6-59 months residing in Matraman District in December 2025. The data was analyzed by Chi-Square test. The results showed that there was no significant relationship between macronutrient intake and BB/U, TB/U, BB/TB. These results show that although the nutritional status of toddlers is generally in the good category, there are still problems related to nutritional consumption patterns and low maternal knowledge that have the potential to affect the nutritional status of toddlers in the future. Therefore, it is necessary to increase nutrition education for mothers under five regarding a balanced diet and meeting nutritional needs according to the age of the child. The next study is recommended to examine other factors related to the nutritional status of toddlers in order to obtain a more comprehensive picture.